2016
DOI: 10.18785/gcr.2701.05
|View full text |Cite
|
Sign up to set email alerts
|

Diets of Atlantic Sharpnose Shark (Rhizoprionodon terraenovae) and Bonnethead (Sphyrna tiburo) in the northern Gulf of Mexico

Abstract: Diets of two coastal sharks, Atlantic Sharpnose Shark (Rhizoprionodon terraenovae) and Bonnethead (Sphyrna tiburo), were examined along the Texas and Alabama coasts in the northern Gulf of Mexico (GOM). Atlantic Sharpnose Sharks were collected from the northwest (n= 209) and northcentral (n= 245) GOM regions while Bonnetheads were collected from two locations within the northwest GOM (Galveston, Texas, n= 164; Matagorda, Texas, n= 79). Dietary analysis was conducted using stomach contents identified to the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…The data provided by Drymon, Powers & Carmichael (2012) and Harrington et al (2016) showed a relationship between the percentage of fishes in the stomach and the length of a shark, with the mean weight (%W) and number (%N) of fishes generally increasing as the shark matured ( Fig. 17 , Appendices 1.35 – 1.36 ).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…The data provided by Drymon, Powers & Carmichael (2012) and Harrington et al (2016) showed a relationship between the percentage of fishes in the stomach and the length of a shark, with the mean weight (%W) and number (%N) of fishes generally increasing as the shark matured ( Fig. 17 , Appendices 1.35 – 1.36 ).…”
Section: Discussionmentioning
confidence: 98%
“…Various studies have shown that the diets of R. terraenovae populations in the northern Gulf of Mexico differ slightly by region as well as ontogenetic stage ( Bethea, Buckel & Carlson, 2004 ; Bethea et al, 2006 ; Drymon, Powers & Carmichael, 2012 ; Harrington et al, 2016 ; Plumlee & Wells, 2016 ; Seubert et al, 2019 ). In the northern Gulf of Mexico, young-of-the-year individuals primarily feed on shrimp, crustaceans, and cephalopods, but they become increasingly reliant on fishes (mainly sciaends and clupeids) through ontogeny.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations